Acquisition as a generator strategy from competitive advantages in the brazilian market of fuels distribuition - Pereira, Maurício Fernandes; Oliveira, Fernando Ventura de (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346599170 The subject from this work is about acquisitions as organizational strategies and it is guided by the general objective on identifying if the acquisition of Texaco by Ultra Group, in Brazil, could generate competitive advantages. Thus, the main aim is to characterize, specifically, the fuel distribution sector in Brazil, presenting characteristics, strategies, classification of resources and the competitive advantage’s identification in the buying process of Texaco by Ultra Group. The methodology used for this research is a case study of qualitative nature. Data collection has been performed through literature review, documentary analysis and semi-structured interviews. In the analysis of collected data, specific objectives have been met. It was clear, therefore, the presence of features such as scale earnings, brand exposure, better management practices, synergies, tangible and intangible assets and market growth. So, those resources are classified according to the competitive implications. Then, it might be concluded that Texaco´s acquisition could bring competitive advantages for Ultra / Ipiranga Group. Respondents believe the sector is growing and businesses tend to grow despite the world crisis. They also confirmed that, in a highly competitive market, strategic alliances and market growing are factors that may ensure success to each company.